Mixed Laryngocele - Ali, Maryam Mohamed; Etbiga, Abdalla Mohamed (Journal of medical and pharmaceutical sciences, 2021)
Laryngocele alludes to dilatation of the saccule of the laryngeal ventricle. It is a rare disease. There are different types, external, internal and mixed. Laryngoceles are more frequently obtained instead of inherent. They are lined by pseudostratified, columnar, ciliated epithelium. Intermittent locales of stratified squamous epithelium (submucosal serous and mucous organs) may be shown. This report describes a 29-year-old Libyan male who had been suffering from left neck swelling for more than 5 years. Over the last months, he had been suffering from the increased size of the swelling but no other clinical symptoms. Linear ultrasound is quite difficult in these cases. A computed tomography scan is the foremost compelling imaging strategy for diagnosis. CT scan helps in deciding the nature, location and sort of laryngocele, and laryngeal structures. other than the follow-up, Surgery is the treatment of choice. Follow up after one year, no recurrence detected.